Medically Attended Influenza During Pregnancy in the 2019–2020 and 2020–2021 Influenza Seasons. Issue 5 (5th November 2022) - Irving, Stephanie A.; Shuster, Elizabeth; Henderson, Jillian T.; Li, De-Kun; Ferber, Jeannette; Odouli, Roxana; Munoz, Flor M.; Nicholson, Erin; Hadden, Louise; Juergens, Mary; Newes-Adeyi, Gabriella; Reichle, Lawrence; et al.
Abstract : No influenza was detected among a cohort of pregnant individuals with respiratory illness from April 2020 through the end of data collection in February 2021. Abstract : Influenza testing and case-confirmation rates in pregnant populations have not been reported during the coronavirus disease 2019 (COVID-19) pandemic. Using electronic medical record data from a cohort of nearly 20, 000 pregnancies in the United States, this retrospective cohort study examines the frequency of acute respiratory or febrile illness encounters, influenza testing, and influenza positivity during the 2020–2021 influenza season, which occurred during the COVID-19 pandemic, compared with the 2019–2020 influenza season, which largely did not. The ratios of influenza tests to acute respiratory or febrile illness visits were similar in the 2019–2020 and 2020–2021 influenza seasons (approximately 1:8 and 1:9, respectively) but were low and varied by study site. Although influenza testing in pregnant patients continued in the 2020–2021 season, when severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) circulation was widespread in the United States, no cases of influenza were identified in our study cohort.